1998
DOI: 10.1136/hrt.79.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and electrophysiological substrates for ventricular tachycardia mapping through the coronary veins

Abstract: Objective-To study the value of epicardial mapping through the coronary venous system in patients with sustained ventricular tachycardia. Design-20 consecutive patients with sustained ventricular tachycardia who were candidates for radiofrequency ablation. Setting-Electrophysiological laboratory. Interventions-Coronary venous angiography was performed with a catheter, which provided coronary sinus occlusion during injection of contrast media. Multipolar microelectrode catheters were then manoeuvred into the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…A 2.5F 16-pole microwire with 2-6-2-mm spacing (Pathfinder, Cardima, Inc, Fremont Calif) was initially positioned along the distal great cardiac vein (GCV) and proximal anterior interventricular vein (AIV). 15 This catheter, or a smaller 1.5F 8-pole version, was subsequently moved to other areas of the coronary venous system as dictated by the ECG and findings of endocardial mapping. Careful attention was given to the proper placement of surface ECG electrodes.…”
Section: Electrophysiological Evaluation Mapping and Ablationmentioning
confidence: 99%
“…A 2.5F 16-pole microwire with 2-6-2-mm spacing (Pathfinder, Cardima, Inc, Fremont Calif) was initially positioned along the distal great cardiac vein (GCV) and proximal anterior interventricular vein (AIV). 15 This catheter, or a smaller 1.5F 8-pole version, was subsequently moved to other areas of the coronary venous system as dictated by the ECG and findings of endocardial mapping. Careful attention was given to the proper placement of surface ECG electrodes.…”
Section: Electrophysiological Evaluation Mapping and Ablationmentioning
confidence: 99%
“…More recent studies suggest that progress in ablation of chagasic VT might be made following new mapping techniques of VT such as epicardial mapping through the coronary venous system 198 or nonsurgical transthoracic epicardial mapping through pericardial puncture 199 . This later investigation found a high prevalence of epicardial reentrant circuits in chagasic VT, reporting that of 10 consecutive patients who underwent transthoracic epicardial mapping, VT was rendered noninducible in all six patients in whom epicardial ablation was attempted 199 .…”
Section: Management Of Chagas' Heart Diseasementioning
confidence: 99%
“…Sustained monomorphic ventricular tachycardia (VT) may also be amenable to percutaneous ablation using catheter-delivered radiofrequency in selected patients with inducible, hemodynamically tolerated VT and identifiable sites of the reentry circuits [195][196][197][198][199] . One of these studies reported that after endocardial radiofrequency ablation in 15 patients, only 4 (27%) patients were free of induced ventricular tachycardia 195 .…”
Section: Management Of Chagas' Heart Diseasementioning
confidence: 99%
“…The GCV has been a target of great interest for idiopathic VT mapping since 1998 when it was described by dePaolaet et al 3 One of the first series looking at using both radiofrequency ablation as well as cryoablation in the GCV region was described in a multicenter case series in 2006. 4 The SPB veins of the GCV may allow for access to otherwise endocardially inaccessible sites.…”
Section: Discussionmentioning
confidence: 99%